Effect of straw on the number of microorganisms and biological activity of soil in crop rotation - A. G. Dzyuin (Аграрная наука Евро-Северо-Востока, 2018)
The intensity of straw decomposition in crop rotation with and without the use of mineral and organic fertilizers and the effect of straw on the number of microorganisms in sod-podzolic soil were studied. The results of the studies were summarized according to the data of two long lasting stationary field experiments conducted at different time. It was established that the process of straw decomposition in the soil is extended in time and develops in stages. In the year of its application the greatest development was obtained by bacteria which used organic nitrogen. On the first_aftereffect of straw, along with the increase in the number of bacteria using organic nitrogen, the process of its decomposition included actinomycetes, fungi and cellulose bacteria. In the third year the number of cellulolytic bacteria and fungi increased. Solid manure and green manure together inhibited the process of straw mineralization. Microorganisms were originally included in the processing of easily degradable green manure and manure and did not react to a hardly decomposable substratum, the straw, its mineralization was moved to the last stage. Liquid manure when mixed with straw was, in general, equal to nitrogen fertilizers. It provided the development of more fungi and cellulolytic bacteria. Bacteria that consume organic nitrogen under the first crop (peas) developed better when the straw was buried at a depth of 20-22 cm compared to surface deposition to a depth of 14-16 cm. The number of fungi and cellulolytic bacteria did not change at the same time. In the second year under the winter rye, the number of actinomycetes increased with incorporation of straw to a depth of 14-16 cm. In the third year, under barley, the straw embedded into 20-22 cm depth positively affected the development of actinomycetes and cellulolytic bacteria. Thus, the incorporation of straw into the traditional depth of the arable layer of 20-22 cm had no negative effect on the development of aerobic bacteria (actinomycetes and cellulolytic bacteria).